2018
DOI: 10.2147/ndt.s171207
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between social and cognitive functions in people with schizophrenia

Abstract: PurposeThe purpose of the present study was to examine clinical factors related to social function in people with schizophrenia.Patients and methodsThe participants were 55 stabilized outpatients with schizophrenia. Their mean age was 39.36 (SD =10.65) years. Social function was assessed using the Quality of Life Scale (QLS). Cognitive function was evaluated with the Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Battery (MCCB). Clinical symptoms were assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…5 Cognitive impairments are correlated with poor clinical outcome and rehabilitation of social function. 6,7 However, the pathophysiological mechanisms underlying the cognitive deficits in SCZ patients are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…5 Cognitive impairments are correlated with poor clinical outcome and rehabilitation of social function. 6,7 However, the pathophysiological mechanisms underlying the cognitive deficits in SCZ patients are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Potential predictors of functional performance have been investigated, and the control of psychotic symptoms alone has been reportedly insufficient for its improvement. Cognitive function can predict subsequent functional performance with an effect size that is greater than the medium range 79. However, the effects of enhancements in cognitive function on functional performance in community can be substantially diminished by several intervening variables, including personal and social factors 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tominaga et al, BACS symbol coding (processing speed) was associated with the total social functioning score, but not other cognitive domains [ 20 ]. Santosh et al reported that among cognitive functions, executive function, verbal working memory, attention, and verbal fluency are related to social functions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia symptoms were evaluated using the PANSS, which includes seven items for positive and negative symptoms and 16 items for general psychopathology [ 19 , 20 ]. The JART50 was used to perform a premorbid intelligence quotient (IQ) evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation